A unique case of development of central retinal vein occlusion in diabetic papillopathy - Kumari, Archana; Lalit Agarwal, Lalit; Agrawal, Nisha; Aditya, Kshitij; Joshi, Ichhya; Pradhan, Deepti (Birat Journal of Health Sciences, 2020)
Diabetic papillopathy (DP) is a rare ocular complication of diabetes presenting as acute disc edema. It is characterized by minimal or no visual symptoms and has tendency to resolve spontaneously in most of the patients with no visual sequel. Visual debility, if present, is attributable to diabetic macular edema (DME), advanced diabetic retinopathy or conversion to ischemic optic neuropathy. We report a case of 33 years old female who presented with bilateral papillopathy with best corrected visual acuity (BCVA) of 6/6 in both eyes. She had associated severe non proliferative diabetic retinopathy but noDME. On follow up, thepatient had good metabolic control and clinical improvement in DP, but she developed sudden diminution of vision in left eye as a result of non ischemic central retinal vein occlusion (CRVO) which was characterized by BCVA of 6/36, dilated tortuous veins and DME. No specific cause of non-ischaemicCRVOwas revealed on detailed work up. Structural and functional improvement was seenon monthly intravitrealanti vascular endothelial growth factor(VEGF) administration.Her BCVA post threeinjectionstood at 6/18. This is to report the possibility of development of CRVO in DP and highlight the need for close follow-up of such patients even in presence of strict diabetic control.